2017
DOI: 10.1007/s10120-017-0732-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of overexpression of NRG1 and its receptors, HER3 and HER4, in gastric cancer patients

Abstract: Neuregulin 1 (NRG1), a ligand for human epidermal growth factor (HER) 3 and HER4, can activates cell signaling pathways to promote carcinogenesis and metastasis. To investigate the clinicopathologic significance of NRG1 and its receptors, immunohistochemistry was performed for NRG1, HER3, and HER4 in 502 consecutive gastric cancers (GCs). Furthermore, HER2, microsatellite instability (MSI), and Epstein-Barr virus (EBV) status were investigated. NRG1 gene copy number (GCN) was determined by dual-color fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…HER4 activation generates two structurally and functionally different isoforms by alternative splicing: CYT1 and CYT2. While the CYT2 isoform can enter the nucleus easily and regulates transcription related to favorable features including cell differentiation, the CYT1 isoform is insufficient to translocate into the nucleus and contains a phosphatidylinositol-3 kinase binding motif to activate its signaling pathway to induce tumor cell proliferation [ 13 , 14 ]. These findings suggested that, as for staining patterns, nuclear accumulation of HER4 might indicate better prognosis, in contrast to cytoplasmic localization that is associated with tumor progression [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HER4 activation generates two structurally and functionally different isoforms by alternative splicing: CYT1 and CYT2. While the CYT2 isoform can enter the nucleus easily and regulates transcription related to favorable features including cell differentiation, the CYT1 isoform is insufficient to translocate into the nucleus and contains a phosphatidylinositol-3 kinase binding motif to activate its signaling pathway to induce tumor cell proliferation [ 13 , 14 ]. These findings suggested that, as for staining patterns, nuclear accumulation of HER4 might indicate better prognosis, in contrast to cytoplasmic localization that is associated with tumor progression [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that, as for staining patterns, nuclear accumulation of HER4 might indicate better prognosis, in contrast to cytoplasmic localization that is associated with tumor progression [ 12 ]. We previously reported that HER4 nuclear expression might be regarded as a favorable prognostic marker in gastric cancer [ 13 ]. However, clinicopathologic significance depending on the subcellular localization of the HER4 protein was not fully evaluated in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HER2 overexpression has been found in approximately 20-30% gastric cancer cases. [10][11][12] Currently, drugs, such as trastuzumab and lapatinib, targeting the HER2-positive gastric cancer are being extensively used as part of the treatment for patients with advanced gastric cancer as they seem to be more effective; 13,14 however, only few studies have been reported on gastric cancer-targeted diagnosis, especially with the HER2 protein as the target.…”
Section: Introductionmentioning
confidence: 99%